Trends in Public Health Research: a Bibliometric Review 2018-2022 - Loso Judijanto; Erny Elviany Sabaruddin; Benny Novico Zani; Musiana Musiana; Siti Misaroh Ibrahim (Yayasan Adra Karima Hubbi, 2024)
As an evolving discipline, public health encompasses many aspects of health, including epidemiology, environmental health, global health, public health interventions, health policy, health promotion, and others. Globally, research in public health continues to increase in line with the increasing complexity of health challenges faced by people in different parts of the world. To understand these research trends, bibliometric studies can provide valuable insights. This study aims to analyze public health research trends from 2018 to 2022 based on indexed scientific publications. By involving the analysis of indexed scientific publications, this objective includes mapping the dominating research themes, identifying the most influential publications, as well as measuring researcher collaboration across institutions. The research method used a bibliometric study conducted using relevant databases to identify, collect, and analyze scientific publications related to public health within the specified time frame. The results of this study show an increase in the number of scientific publications in public health research during the period 2018-2022. Dominating themes include global health issues, public health interventions, epidemiology, and environmental health. In addition, collaboration between researchers was also noted to increase, indicating a synergized effort in addressing public health issues across disciplines and countries. The conclusions of this study provide an in-depth understanding of public health research trends over the period, highlighting key foci and developments in the discipline. These results can help guide future research directions in support of global public health efforts.